Treatment of tobacco dependence in cancer patients - Recommendations of the Section of Supportive Treatment and Care and the Section of Preventive Oncology of the Czech Cancer Society of the Czech Medical Association of J. E. Purkyně, Working Group for t… - Zvolská, K; Králíková, E; Vokurka, S; Halámková, J; Strnadová, A (Klinicka onkologie, 2024)
Smoking is a significant risk factor for the development of many cancers. In addition, after a cancer dia-gnosis, it also has an adverse effect on survival, the course and effectiveness of cancer treatment and quality of life, and increases the likelihood of a number of other complications. Treating tobacco dependence reduces the risk of their occurrence or the extent of their consequences. A working group of authors from professional groups (the Section of Supportive Treatment and Care and the Section of Preventive Oncology of the Czech Society of Oncology of the Czech Medical Association of J. E. Purkyně, the Society for the Treatment of Tobacco Dependence, Czech Nurses Association, Working Group for the Prevention and Treatment of Tobacco Dependence of the Czech Medical Association J. E. P. and the Society for Treatment of Tobacco Dependence) prepared a simple basic scheme of intervention in contact with smokers in routine practice based on recommendations of professional societies, outcomes of studies, scientific literature and proven practice. A smoke-free environment, the importance of zero exposure to tobacco smoke, smoking cessation recommendations for smokers, relapse prevention for ex-smokers and the offer of tobacco dependence treatment should be a natural part of cancer care at least in the form of a brief DIK (abbreviation for "question - intervention - contact" in the Czech language) intervention. It is important to record smoking status, including exposure to second-hand smoke, in all patients, and to empathically repeat interventions in smokers (active and passive), including relapse prevention. This ap-proach contributes to abstinence in cancer patients and thus to higher efficacy of cancer treatment, longer survival and reduction of other risks.
Keywords: Societies, Medical; tobacco dependence; Česká republika; společnosti lékařské; smoking; Czech Republic; psychosocial intervention; Neoplasms; Smoking Cessation; pharmacotherapy; Humans; Tobacco Use Disorder; nádory; poruchy vyvolané užíváním tabáku; Clinical oncology; tobacco use disorder; heart failure; odvykání kouření; lidé